A new wine Torulaspora delbrueckii killer strain with broad antifungal activity and its toxin-encoding double-stranded RNA virus - Ramírez, Manuel; Velázquez, Rocío; Maqueda, Matilde; López-Piñeiro, Antonio; Ribas, Juan C. (Frontiers in Microbiology, 2015)
Wine Torulaspora delbrueckii strains producing a new killer toxin (Kbarr-1) were isolated and selected for wine making. They killed all the previously known S. cerevisiae killer strains, in addition to other non-Saccharomyces yeasts. The Kbarr-1 phenotype is encoded by a medium-size 1.7 kb dsRNA, TdV-Mbarr-1, which seems to depend on a large-size 4.6 kb dsRNA virus (TdV-LAbarr) for stable maintenance and replication. The TdV-Mbarr-1 dsRNA was sequenced by new generation sequencing techniques. Its genome structure is similar to those of S. cerevisiae killer M dsRNAs, with a 5´-end coding region followed by an internal A-rich sequence and a 3´-end non-coding region. Mbarr-1 RNA positive strand carries cis acting signals at its 5´ and 3´ termini for transcription and replication respectively, similar to those RNAs of yeast killer viruses. The ORF at the 5´ region codes for a putative preprotoxin with an N-terminal secretion signal, potential Kex2p/Kexlp processing sites, and N-glycosylation sites. No relevant sequence identity was found either between the full sequence of Mbarr-1 dsRNA and other yeast M dsRNAs, or between their respective toxin-encoded proteins. However, a relevant identity of TdV-Mbarr-1 RNA regions to the putative replication and packaging signals of most of the M-virus RNAs suggests that they are all evolutionarily related.